A Critique of Pridi Panomyong's Economic Plan - Youngmevittaya, Wanpat (รัฐศาสตร์นิเทศ, 2023)
This paper deals with Pridi Panomyong's Economic Plan (the PEP). Published shortly after the Siamese Revolution in March 1933, the PEP was originally attacked for its alleged Stalinism, but with the rehabilitation of Pridi from the 1980s, by both left and liberal leaning scholars, the PEP was reinterpreted as evidence of Pridi's social democracy – liberalism with the soft socialism elements. For many contemporary scholars, the PEP is not a radical plan; instead, it offers a modest economic program similar to a modern welfare state. They also believe that the PEP is desirable because they believe that if it had been implemented it would have realized economic justice. This paper reexamines the veracity of these perceptions of the PEP, and argues that the PEP is much more radical than it is now being perceived, and that it is indefensible because it would undermine economic self-determination and the status of democratic citizenship. The PEP would turn citizens into state functionaries rather than free citizens able to exercise their economic self-determination, and they would need to trust a central government rather than themselves and their fellow nationals.